Relationship between Physical Activity and Fatigue in Adults with Cystic Fibrosis. - Orava, Carly; Fitzgerald, Jennifer; Figliomeni, Stephen; Lam, Danette; Naccarato, Anthony; Szego, Erika; Yoshida, Karen; Fox, Pat; Sykes, Jenna; Wu, Kenneth (Physiotherapy Canada)
Purpose: We examined the relationship between the amount of physical activity and level of fatigue in adults with cystic fibrosis (CF). Method: Participants were recruited from the Toronto Adult Cystic Fibrosis Centre at St. Michael's Hospital. Participants completed the Habitual Activity Estimation Scale, the Multidimensional Fatigue Inventory, and the Depression subscale of the Hospital Anxiety and Depression Scale, in that order. Descriptive statistics and linear and multiple regressions were computed. Results: Over a 6-month period, 51 individuals were approached, and 22 (10 men, 12 women) participated in this study. The participants' median age was 33, and forced expiratory volume in 1 second (FEV1) was 64% predicted. When holding both FEV1 and depression constant, a significant negative correlation was found between total active hours per weekday and general fatigue (β=–0.735, p=0.03); there was a negative trend between total active hours per weekday and physical fatigue (β=–0.579, p=0.09). Conclusions: This study is the first to demonstrate that among adults with CF, a higher level of physical activity is associated with a lower level of general and physical fatigue when controlling for lung function and level of depression. Physical activity may be used as a means of mitigating the levels of general and physical fatigue in people with CF.